Dimensioning of a 3D object recovered from a 2D sketch - Ramaiyan Murali (2008)
A system has been developed in NTU that reconstructs the 3D object depicted in a 2D sketch. As the 3D model is directly reconstructed from 2D sketch, it does not have proper dimensions. This dissertation reports on the project that attempts to provide dimensions to the model. While giving the dimension, geometrical relationships within the model such as parallel and perpendicular faces and face planarity will not be disturbed.